Sustainable process engineering : prospects and opportunities - Kołtuniewicz, Andrzej (De Gruyter textbook., 2014)
The vital need for alternative resources and reaction routes, environmentally friendly and economically feasible industrial chemical processes has become a ubiquitous reality. This very timely introductory text covers new materials, processes and industry sectors: nanotechnology, microreactors, membrane separations, hybrid processes, clean technologies, energy savings and safe production of energy, renewables and biotechnology. Some completely new processes for the solid-liquid systems are also discussed in detail, thus creating new opportunities of sustainable development not only in industri.